2018
DOI: 10.3846/ijspm.2018.443
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Spatial Variation in Housing Construction Activity in Turkey

Abstract: In Turkey, there has been a strong policy narrative that has emphasized the importance of construction activity as a driver of economic growth. This has given shape to a central state-led policy regime that has sought to ensure that planners and other urban policy makers develop plans and strategies that support construction activity. Against this backdrop, and a recent history of uneven spatial development, this paper seeks to understand what this policy imperative might mean for housing construction activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In addition to this, it is obvious that the luxury housing projects, represented in this paper with property-led regeneration on large size parcels also affect the land and real estate values globally. Among entire provinces, Istanbul is the most appreciated province in Turkey, in terms of construction and housing market, represented by highest increase in housing prices and mortgage credit use (Alkay et al, 2018). This rise in economic value is another important consequence, and it should be questioned if these values are speculative in local neighbourhood level, as well.…”
Section: Physical -Structural Characteristics Of the Building Renewalmentioning
confidence: 99%
“…In addition to this, it is obvious that the luxury housing projects, represented in this paper with property-led regeneration on large size parcels also affect the land and real estate values globally. Among entire provinces, Istanbul is the most appreciated province in Turkey, in terms of construction and housing market, represented by highest increase in housing prices and mortgage credit use (Alkay et al, 2018). This rise in economic value is another important consequence, and it should be questioned if these values are speculative in local neighbourhood level, as well.…”
Section: Physical -Structural Characteristics Of the Building Renewalmentioning
confidence: 99%
“…It was revealed that the growth of the volume of realized construction products, shows the way out of the country's economic crisis. The confirmation of the construction development importance is the study of spatial planning of state-owned construction in Turkey [17]. The relationship between the priorities of the state economic policy and market development was determined and the level of construction activity was the main factor influencing the formation of the spatial development imperatives.…”
Section: The Statement Of Basic Materialsmentioning
confidence: 99%
“…The activities of the construction industry have great significance in relation to the achievement of the national socio-economic development goals of providing shelter, infrastructure and employment [20][21][22][23]. Bon [24] notes that construction activity has a global dimension, with activity spilling over from advanced economies, with high levels of capital, to emerging and developing market contexts.…”
Section: Introductionmentioning
confidence: 99%